A mechanically self-locked gemini-[1]rotaxane-assembled microsphere and its properties on l-Arg controlled reversible morphology and fluorescence changes. Issue 32 (29th July 2021) - Zhang, Yun-Fei; Li, Ying-Jie; Wang, Zhong-Hui; Sun, Xiao-Wen; Yang, Qing-Yu; Dong, Hong-Qiang; Zhang, You-Ming; Wei, Tai-Bao; Yao, Hong; Lin, Qi
Abstract : A novel pillar[5]arene-based gemini-[1]rotaxane DEP5 was successfully designed and synthesized, the morphology and fluorescent properties of the gemini-[1]rotaxane DEP5 could be reversibly controlled by alternative addition of l -Arg and TFA. Abstract : Herein, a novel pillar[5]arene-based gemini-[1]rotaxane molecule DEP5 was successfully designed and synthesized. Interestingly, the gemini-[1]rotaxane DEP5 serving as a chemosensor could selectively recognize l -Arg with high sensitivity and its lowest detection limit (LOD) was 1.43 × 10 −7 M. Simultaneously, the gemini-[1]rotaxane DEP5 could assemble into the microsphere structure and its microsphere morphology could transform into cross-linked supramolecular networks through host–guest interactions with l -Arg. Furthermore, its microsphere morphology could be recovered again by the addition of competitive reagent guest trifluoroacetic acid (TFA). Therefore, this work provides a new and simple approach to construct gemini-[1]rotaxane-based smart materials which could assemble into the microsphere in solution and achieve reversible regulation of morphology between the microsphere and cross-linked supramolecular networks by external chemical stimuli (l -Arg/TFA). This kind of material not only has a perspective in l -Arg sensors but also has potential for application in other fields such as drug control release.